Visual and Textual Elements through Peirce’s Analysis of Persib Supporters’ Choreography on the Republikbobotoh TV Youtube Channel - Chaniago, Muhammad Daffa; Suswanto, Deni; Sakinah, R. Myrna Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
This research analyzes the choreography of Persib supporters on the REPUBLIKBOBOTOHTV YouTube channel. Supporter choreography is important and influential in matches based on the meaning to be conveyed. The analysis of visual and textual elements, using Peirce's semiotic perspective, aims to find out the meaning conveyed by the choreography presented. In this research, the method used is descriptive qualitative method. The results show the various meanings and purposes of the choreography. Pennywise's choreography shows how a form of psychological threat aims to influence the opponent. The Viking choreography shows a pride that has a meaning of how a long journey of history is achieved. In the Wizard choreography shows how the persib team must be able to control the game as a form of direct support in order to increase the motivation and mentality of the team.